The Inhibition of Mild Steel Corrosion by Sulphur Containing Organic Compound (Albayan Scientific Journal, 2023)
The inhibition of mild steel corrosion in "2.0 M sulphuric acid" solution by a Sulphur containing organic ompound namely " Methyl Carbazodithoate " has been studied at temperature 30 ℃ by weight loss technique. Adsorption isotherms were tested for their relevance to describe the adsorption behavior of methyl carbazodithoate. The experimental results show that the test inhibitor has a promising inhibitory action against corrosion of low carbon  steel in  the  medium  investigated. The inhibition efficiency was found to increase with a corresponding  increase in the concentration of the  inhibitor.The adsorption mechanism of methyl carbazodithoate inhibition is also proposed. The lower adsorption of sulphate ions on the carbon steel metal surface permits more space for the adsorption of inhibitor molecules and enhances inhibition of corrosion. Finally, the obtained results in this work indicates that the sulphur-containing inhibitor compound namely; "methyl carbazodithoate" compound is an effective inhibitor for corrosion inhibition of carbon steel in sulphuric acid solution.
Keywords: Corrosion Inhibitors; methyl carbazodithoate; mild steel; Inhibitor efficiency.